Synaptic integration gradients in single cortical pyramidal cell dendrites - Branco, Tiago (Neuron, 2011)
Cortical pyramidal neurons receive thousands of synaptic inputs, arriving at different dendritic locations with varying degrees of temporal synchrony. It is not known if different locations along single cortical dendrites integrate excitatory inputs in different ways. Here we have used 2-photon glutamate uncaging and compartmental modelling to reveal a gradient of non-linear synaptic integration in basal and apical oblique dendrites of cortical pyramidal neurons. Excitatory inputs to the proximal dendrite sum linearly and require precise temporal coincidence for effective summation, whereas distal inputs are amplified with high gain and integrated over broader time windows. This allows distal inputs to overcome their electrotonic disadvantage, and become surprisingly more effective than proximal inputs at influencing action potential output. Thus, single dendritic branches can already exhibit non-uniform synaptic integration, with the computational strategy shifting from temporal coding to rate coding along the dendrite.